Jual Beli Valuta Asing dalam Ekonomi Islam - Khotibul Umam (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2020)
Foreign exchange market (Forex) is a transaction under the scope of Islamic economic studies. It is lawfully allowed as long as not violating shariah principles. This is valid particularly for the spot type because it fulfills the requirement of yadan bi yadin, namely cash transaction with the same value. As for the forward, swap and opsi types are considered unlawful as they contain random speculation (gharar) unsure. However, some Islamic scholars allow the forward when aiming to fulfill the need instead of speculation purpose, such as protecting hedging in anticipating the risk of foreign currency fluctuation used as international payment instrument.